2017
DOI: 10.1016/j.ijhcs.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

When we talk about older people in HCI, who are we talking about? Towards a ‘turn to community’ in the design of technologies for a growing ageing population

Abstract: This paper addresses a number of challenges HCI designers and researchers deal with when designing digital technologies for older people. We conducted a 5-year research-through-design study, which combined ethnography, participatory design and real-life evaluation, to explore the design and use of technologies aimed to enhance the social life of older people. The paper explores widespread assumptions about the social category of older people and the meaning of technologies for them. This paper argues that assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 62 publications
0
59
0
2
Order By: Relevance
“…However, there is no consensus on its characteristics; since researchers have recognized that older people are a very heterogeneous set of users in regards to their experiences, skills, health status, and abilities. Moreover, other previous studies have suggested that a high amount of HCI research presents older adults as a homogeneous category, that is, a set of users with common needs, abilities, and interests [ 46 ].…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus on its characteristics; since researchers have recognized that older people are a very heterogeneous set of users in regards to their experiences, skills, health status, and abilities. Moreover, other previous studies have suggested that a high amount of HCI research presents older adults as a homogeneous category, that is, a set of users with common needs, abilities, and interests [ 46 ].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Second, the heterogeneous vision, which delivers a more realistic picture of older people, assumes that these people would have a categorization that is easier to define. For example, some studies specified adulthood as the relevant criterion for characterization, although others focused on personal skills or the different transitions experienced in the stages of their lives [ 46 , 47 ].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…aged 60 and over (10.9%). Studies conducted by for example Shamim et al (2016) and Righi et al (2017) show that there the age was found to be significant for visual appeal, comprehensiveness, intuitiveness, and pre-knowledge requirement but there is also no need to focus on design for older people but focus on the useful and also usable design for an average user. And not only in the way of ergonomics, usability and design, but also in the social role.…”
Section: Discussionmentioning
confidence: 99%
“…10. To set up experiments, the speed of AVs randomly set to [2][3][4]. Where, each test has been executed 5 times and saved in the log file…”
Section: Testing and Evaluationmentioning
confidence: 99%
“…Extensive research has been done in HCI to make systems autonomous. Valeria et al [2] have evaluated the factors played by psychology in designing systems. The role of HCI is vast and applies to many unique types of systems.…”
Section: Introductionmentioning
confidence: 99%